Web-Based Intervention for Postpartum Depression: Formative Research and Design of the MomMoodBooster Program - Danaher, Brian G; Milgrom, Jeannette; Seeley, John R; Stuart, Scott; Schembri, Charlene; Tyler, Milagra S; Ericksen, Jennifer; Lester, Whitney; Gemmill, Alan W; Lewinsohn, Peter (JMIR Research Protocols, 2012)
BackgroundPostpartum depression is a significant public health problem affecting approximately 13% of women. There is strong evidence supporting Cognitive Behavioral Therapy (CBT) for successful psychosocial treatment. This treatment model combines cognitive and behavioral strategies to address pessimism, attributions for failure, low self-esteem, low engagement in pleasant activities, social withdrawal, anxiety, and low social support. Encouraging results have been reported for using Web-based CBT interventions for mental health domains, including the treatment of panic disorder, post-traumatic stress disorder, and complicated grief and depression. To date, however, Web-based interventions have not been used and evaluated specifically for the treatment of postpartum depression. ObjectiveWe describe the formative work that contributed to the development of our Web-based intervention for helping to ameliorate symptoms of postpartum depression, and the design and key components of the program. MethodsA total of 17 focus group participants and 22 usability testers, who shared key characteristics with the participants of our planned feasibility study, took part. ResultsThe qualitative and quantitative data gathered in the focus groups and usability sessions reported here suggest that the new mothers involved had largely positive reactions to the major features of the program and that those program features performed well in terms of usability. ConclusionsAn overview of the eventual design, architecture, and key program ingredients of the MomMoodBooster program is provided including innovative features supplementing 6 core CBT sessions, which include a partner’s website, a library, and individual feedback by a personal coach.